Effect of Jameed Form on the Chemical Composition, Rheological and Microbial Properties - Hamad, Mohamed N. F; Ismail, Magdy M; El-Menawy, Reham K. A (Journal of Food Technology Research, 2016)
Nine treatments to study the effect of jameed form (triangle, square and cylinder molds) on the chemical composition, rheological and microbial properties. The treatments were made as follow: (A) sheep buttermilk (control) with ball form, (B) goat skim milk with ball form, (C) goat skim milk with triangle form, (D) goat skim milk with square form, (E) goat skim milk with cylinder form, (F) cow skim milk with ball form, (G) cow skim milk with triangle form, (H) cow skim milk with square and (I) cow skim milk with cylinder form. Yield of cylindrical shape were slightly higher, while levels of ball, triangle and square forms were close to each other. The lowest acidity levels were detected in cylindrical form. Square and cylinder forms were recorded the lowest of TS, fat, total protein and ash values. Square and cylinder forms possessed the lowest TVBC, LAB and proteolytic bacteria. The triangle or square molds caused significant (p<0.05) increase in wettability, where square form scored the highest syneresis levels among different shapes. The spherical and cylindrical shapes had the minimum values of hardness, cohesiveness, gumminess and chewiness whereas the triangle and square forms possessed the maximum levels.